Analysis of Project Time Using the Earned Value Method Concept on the Situbondo District Bagor Bridge Replacement Project - Putranto, Yonandika Pandu; Patriadi, Andi; Sajiyo, Sajiyo (Transpublika Publisher, 2025)
This research aims to analyze the time and cost efficiency of the Bagor Bridge Replacement Project in Situbondo Regency using the Earned Value Method. The research employs a qualitative descriptive approach, where data is collected through literature studies, field observations, and analysis of project documents such as plan drawings and weekly reports. Data analysis techniques include calculating several indicators, including Cost Performance Index (CPI), Schedule Performance Index (SPI), and Variance at Completion (VAC). The results showed that in weeks one to nine, the project ran according to the planned schedule, but there was a delay between weeks ten to nineteen. In the twentieth to twenty-fourth week, the project made progress again. The effectiveness of project time and cost control was obtained with a score value of 1.603, which indicates that project control is very effective. Based on these results, it is recommended that the implementing contractor compile detailed daily reports to monitor cost overruns and anticipate existing risks. The use of Earned Value method can be combined with other methods to maximize project control. In addition, logistics, equipment, and resource management should be considered to prevent unwanted problems.